G20(P) Paediatricians' and GPs' Understanding of the "Medicine Not-Licenced For Use in Children". (4th June 2013) - Baba, M
Abstract : Background: Marketing authorization (MA), previously known as product licence, is what is referred to when talking about "medicines not-licenced for use in children". Medicines Act and the RCPCH/NPPG policy statement support and give guidance on use of such drugs, which is about 75% of prescribing in Paediatrics. Their use is even more in sub-specialties, creating much anxiety in GPs who are asked to prescribe. Increasingly, the hospital pharmacy is dispensing these "specialist drugs" that have been refused dispensation in the community, often due to misunderstanding about MA. Aim: To investigate the understanding of the term "not-licenced for use in children" by GPs and Paediatricians. Methods: A questionnaire with a multiple choice question asking what "not-licenced for use in children" means was administered at various meetings for GPs and Paediatricians over a two-week period. The choice of answers were; "Illegal to supply for children's use", "Illegal to prescribe for children", "Safety in children untested", "Efficacy in children untested", "Not to be marketed for children's use" and "Pharmacists require special authorisation by prescriber". Respondents chose as many answers as they thought applicable. Results: There were 80 respondents; 46 Paediatricians (14 consultants and 32 trainees), 29 GPs (15 prescribing leads and 14 trainees) and 5 Foundation Year doctors. Overall, "Safety untested" was the most frequent answer (61%) followed by "Not to be marketed"(58%), and "Efficacy untested"(48%). 8(10%) trainees thought supplying unlicensed drugs was illegal and 7(6 trainees, 1 consultant (9%)) thought it was illegal to prescribe. More consultants knew that "licence" means marketing authorisation(86%) while about a half(47%) of the GP prescribing leads did.(Graph1) However, more GPs chose purely correct answer i.e. "not for marketing" (33%), followed by consultants (29%). The absence of safety and efficacy testing in children may have been true for drugs developed before 2007 when the Paediatric Regulations came into force. Allowing for this 58% of consultants and 46% of qualified GPs gave the correct combination of answers. Conclusion: The lack of understanding about MA is evident among Paediatricians and GPs, many linking the licencing directly with safety. There is a scope for education, promoting efficiency and safety of prescribing in hospitals and community.